PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN JASA KEUANGAN DI BURSA EFEK INDONESIA - Sulistiani, Sulistiani; Meutia, Rita (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study aims to determine the effect of company size, profitability, liquidity, and leverage on bond ratings at financial service companies on the Indonesian Stock Exchange (BEI). The samples in this study consisted of 20 companies obtained by the purposive sampling method. The type of data used secondary data from financial statement report during the period 2014-2018 download from www.idx.co.id. The data analysis method in this study was logistic regression analysis through of SPSS. The results of study stated that company size has a significant positive effect on bond ratings, profitability has a negative and insignificant effect on bond ratings, liquidity and leverage have negative significant effect on bond ratings